STUDI POTENSI PENDANAAN CLIMATE CHANGE PADA LEMBAGA KEUANGAN MULTILATERAL - Nurhidayat, R.; Setiawan, Sigit (Badan kebijakan Fiskal, 2011)
Climate Change has adversely brought impacts to a large number of countries all over the globe, including Indonesia. The issues regarding climate change impacts have become primary concerns in managing sustainable economic development in Indonesia. In striving to tackle those impacts, funding will be a key element. While the State Budget has allocated a particular amount of funding, other sources of external funding is actually expected, including those from multilateral financial institutions. ADB is one of the multilateral donor institutions that provide climate change adaptation and mitigation related fund. In this study, the potentially utilized financing sources of the donor institution by Indonesia is explored, both solely from the individual institution or in cooperation with other donors. The potential financing source aspects which are analyzed cover funding mechanisms, types of funding, and the fund allocation provided. Other key aspects such as assessment and evaluation criteria employed by ADB to approve a particular project to finance under its portfolio are also explored, completed with several project examples under ADB funding.